Integrasi Nilai-Nilai Al-Qur'an dan Teori TQM dalam Peningkatan Mutu Pendidikan Islam - Muhammad Adham Baehaqi (Indo Publishing, 2026)
The quality of education is a strategic issue that continues to be a major concern in the management of Islamic educational institutions. On one hand, the Qur'an as the primary source of values for Muslims has given strong signals about the importance of quality in every dimension of life through the concepts of ihsan, amanah, and planning. On the other hand, the modern management world has produced various theories and quality improvement approaches known as Total Quality Management (TQM), developed by figures such as W. Edward Deming, Fred Smith, Joseph M. Juran, Philip B. Crosby, and Edward Sallis. This article aims to examine in depth how Qur'anic values can be integrated with TQM theory in efforts to improve the quality of Islamic educational institutions. The method used is library research with a descriptive-analytical and comparative approach. The results show that there is significant alignment between Qur'anic values and TQM principles, so that the integration of both can serve as a solid foundation for building a quality culture in Islamic educational institutions